Embracing the Tension: A New/Ancient Approach to Problem Solving - Rick Olsen (Academic Chairpersons Conference Proceedings, 2023)
This workshop will illuminate four important concepts and approaches to problem solving and problem navigation. Participants will then work individually and collectively around problems of shared interest to deepen their understanding of these concepts. The running example by the facilitator will be faculty retirements.
Keywords: problem-solving; leadership; tensions; navigation; retirement